Prevalence and contributing factors of depression among women with infertility in low-resource settings: a systematic review and meta-analysis - Tadesse, Shimelis; Kumsa, Henok; Kitil, Gemeda Wakgari; Chereka, Alex Ayenew; Gedefaw, Getnet; Chane, Fiker; Mislu, Esuyawkal (Frontiers in Medicine, 2025)
BackgroundDepressive symptoms are the most common manifestations of psychiatric disorders among women with infertility. In low-resource settings, the overall prevalence and contributing factors of depressive symptoms among women with infertility remain unknown.ObjectivesTo estimate the prevalence and contributing factors of depression among women with infertility in low-resource settings.MethodsA review was conducted using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The PubMed, MEDLINE, Google Scholar, and Cochrane databases were used to identify eligible studies published up to 30 November 2024. Three authors independently extracted the data. Studies that reported depression among women with infertility were included in this review. The data were analyzed with STATA version 14, and a meta-analysis was conducted using a random-effects model. Publication bias and heterogeneity were assessed via Eager’s tests and I2. Subgroup and sensitivity analyses were performed to identify the potential source/s of heterogeneity. A p-value of 0.05 was declared as statistically significant. The findings were synthesized and presented using texts, tables, and forest plots with measures of effect and 95% confidence interval (CI).ResultsSeventeen published cross-sectional studies that met the inclusion criteria with a total of 3,528 women with infertility were selected for this study. The pooled prevalence of depression among women with infertility was 48.77% (95% CI (35.86, 61.67). Good functioning family {OR 0.71 [95% CI (0.51, 0.97), I2: 0.00%]}, good husband support {OR 0.52 [95% CI (0.34, 0.79), I2: 0.00%]}, primary infertility {OR 2.55 [95% CI (1.36, 4.79), I2: 68.53%]}, history of divorce {OR 4.41 [95% CI (2.11, 9.24), I2: 0.00%]}, and duration of infertility lasting more than 10 years {OR 6.27 [95% CI (2.74, 14.34), I2: 15.26%]} were statistically significant.ConclusionDepression was high among women with infertility in low-resource settings such as Africa compared to those in high-income countries, men, and pregnant mothers. Good functioning family, good husband support, primary infertility, history of divorce, and duration of infertility lasting more than 10 years were statistically associated. Therefore, African countries and the stakeholders in collaboration with mental health experts and gynecological care providers should address these problems in order to reduce or prevent depression among women with infertility.Systematic Review RegistrationPROSPERO (ID: CRD42024516458).